PENGARUH SISTEM PENGENDALIAN INTERN DAN KOMPETENSI MANAJER KEUANGAN TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH - Pratiwi, Wallensy Septi; Nurazi, Ridwan; Puspita, Lisa Martiah Nila (JURNAL FAIRNESS, 2018)
The purpose of this research is to analyze the influence of the government’s internal control system, the competence, and the educational background of the financial management officers toward the quality of government of finance report. This research was conducted in the Ministry of Religius Affairs of Bengkulu Province. The populations of this research were all financial management officers from one regional office and 10 districts residing in the Ministry of Religius Affairs of Bengkulu Province which have a working period of more than one year. The data are collected from 100 financial administrators through questionnaires. The data analysis method of this research was multiple linear regressions. The results show that the government’s internal control system, and the competence have a positive effect on the quality of government of finance report. Meanwhile, the educational background does not have effect on the quality of government of finance report. The implication of this research is to produce quality of financial reports at the Ministry of Religius Affairs of Bengkulu Province, conducted with applying the internal control system, and improving employee competency.